2013
DOI: 10.1007/jhep03(2013)085
|View full text |Cite
|
Sign up to set email alerts
|

Heterotic-type II duality in twistor space

Abstract: Heterotic string theory compactified on a K3 surface times T 2 is believed to be equivalent to type II string theory on a suitable Calabi-Yau threefold. In particular, it must share the same hypermultiplet moduli space. Building on the known twistorial description on the type II side, and on recent progress on the map between type II and heterotic moduli in the limit where both the type II and heterotic strings become classical, we provide a new twistorial construction of the hypermultiplet moduli space in thi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 71 publications
(148 reference statements)
0
13
0
Order By: Relevance
“…Even within the realm of N = 2 compactifications, we have focused on the easier half of the problem, the vector multiplet moduli space. Recently there has been some remarkable work on the understanding of quantum corrections to the hypermultiplet moduli space [73][74][75][76][77][78][79][80][81][82][83][84][85][86][87] (see also [88] for a nice review of many of these results), and it would also be illuminating to carry over these results to the context of F-theory compactifications, as we have done here for the vector multiplet moduli space.…”
Section: Discussionmentioning
confidence: 99%
“…Even within the realm of N = 2 compactifications, we have focused on the easier half of the problem, the vector multiplet moduli space. Recently there has been some remarkable work on the understanding of quantum corrections to the hypermultiplet moduli space [73][74][75][76][77][78][79][80][81][82][83][84][85][86][87] (see also [88] for a nice review of many of these results), and it would also be illuminating to carry over these results to the context of F-theory compactifications, as we have done here for the vector multiplet moduli space.…”
Section: Discussionmentioning
confidence: 99%
“…where Re s is the area of the base P of the K3 fibration, so the large volume limit ρ → −∞ on the heterotic side corresponds to g (4) → 0 and Re s → +∞ on the type IIB side. The ten-dimensional string coupling is however finite in this limit [20],…”
Section: Heterotic/type II Duality In Hypermultiplet Sectormentioning
confidence: 98%
“…does depend on all Kähler moduli except s, and includes effects of all worldsheet instantons wrapping the two-cycles γ i , γ α , in addition to the classical cubic contribution, because the Kähler moduli t i , t α stay finite in the large volume limit ρ → −∞ on the heterotic side. In [19,20], it was shown that in the absence of reducible singular fibers, the QK metric derived from the leading term (3.3) describes the symmetric space SO(4, n)/SO(4) × SO(n), reproducing the expected hypermultiplet moduli space for heterotic strings compactified on K3 equipped with a rigid gauge bundle. Under this identification, the heterotic and type II variables were related by (3.1) supplemented by…”
Section: Heterotic/type II Duality In Hypermultiplet Sectormentioning
confidence: 99%
See 2 more Smart Citations